SEJARAH DAN MAKNA RUMAH ADAT DI DESA MORAMAM, KECAMATAN ALORBARAT DAYA KABUPATEN ALOR - Matias Lau Mau Pating; Muhamad Songge, Onarita Lanoni, Uriana Mabileti, Marsia Alomau, Martha Lanmai, Jennie Tunliu, Paulin (CV. ADIBA AISHA AMIRA, 2025)
This research examines the uniqueness of the History and Meaning of Traditional Houses in Moramam Village, Alorbarat Daya District, Alor Regency, The research method used is a qualitative method with an ethnographic approach, which involves direct observation, in-depth interviews with traditional elders, as well as the study of related literature. The results showed that traditional houses in Moramam Village have distinctive architecture that reflects the cultural identity of the Alor community. The building structure consisting of strong wooden pillars symbolises community resilience, while the conical roof reflects the harmonious relationship between humans and nature and ancestors. In addition, the traditional house also functions as a place to hold traditional ceremonies and community deliberations. Thus, the traditional house in Moramam Village is not just a place to live, but also the centre of social and cultural life that has been passed down from generation to generation. This research is expected to be a reference in efforts to preserve traditional houses as part of national cultural wealth. In addition, this research also reveals various challenges in the preservation of traditional houses, including changes in people's lifestyles, the influence of modernisation, and the lack of attention from related parties. Therefore, collaborative efforts between the community, government, and academics are needed to maintain the sustainability of traditional houses as local cultural identities.